1992
DOI: 10.1172/jci115808
|View full text |Cite
|
Sign up to set email alerts
|

A new variant of Glanzmann's thrombasthenia (Strasbourg I). Platelets with functionally defective glycoprotein IIb-IIIa complexes and a glycoprotein IIIa 214Arg----214Trp mutation.

Abstract: We describe a new variant of Glanzmann's thrombasthenia (variant Strasbourg I). The patient (M.S.) showed an absence of platelet aggregation to ADP, thrombin, and collagen, and a decreased clot retraction. Platelet fibrinogen was -20% of normal levels. ADP-stimulated platelets bound markedly reduced amounts of soluble fibrinogen and platelet adhesion to surface-bound fibrinogen was defective. Normal to subnormal amounts of glycoprotein (GP) Ilb-Illa (am,83) complexes, the platelet fibrinogen receptor, were rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
67
0
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 134 publications
(74 citation statements)
references
References 72 publications
6
67
0
1
Order By: Relevance
“…Two variant type GT mutations in ␤ 3 , Asp119Tyr and Arg214Trp, were examined in parallel as negative controls. 37,38 As expected, Asp119Tyr and Arg214Trp mutations abolished the ligand binding function of both ␤ 3 integrins. Neither His280Pro nor Cys374Tyr mutation impaired the ligand binding to both ␣ IIb ␤ 3 and ␣ v ␤ 3 .…”
supporting
confidence: 76%
“…Two variant type GT mutations in ␤ 3 , Asp119Tyr and Arg214Trp, were examined in parallel as negative controls. 37,38 As expected, Asp119Tyr and Arg214Trp mutations abolished the ligand binding function of both ␤ 3 integrins. Neither His280Pro nor Cys374Tyr mutation impaired the ligand binding to both ␣ IIb ␤ 3 and ␣ v ␤ 3 .…”
supporting
confidence: 76%
“…Both naturally occurring and induced mutations (24,27,28,60,61) in this segment can abolish Fg binding to ␣ IIb ␤ 3 ; RGD ligand peptides are cross-linked to this region of the receptor (9,62), and peptides from this segment can bind ligands (26,36). Alemany et al (56) have previously expressed ␤ 3 -(274 -368) and reported that it bound Fg but in a divalent ion-independent manner.…”
Section: Discussionmentioning
confidence: 99%
“…by guest www.bloodjournal.org From and 1 from Australia; all with moderate to severe bleeding, Table 1) possessed homozygous substitutions of Arg214 (Arg214Gln or Trp) in the ADMIDAS (adjacent to MIDAS) Ca 2ϩ -binding domain of ␤3 (Figure 2). [32][33][34][35][36][37] These substitutions made ␣IIb␤3 unstable, sensitive to divalent-cation chelation, and unable to bind Fg; they not only prevent aggregation, they also stop clot retraction and platelet Fg capture, reinforcing the idea that ␣IIb␤3 is required for each task. Although 3-dimensional structures of the unactivated and activated (Fg-binding) forms of ␣IIb␤3 have been defined and key residues essential for Fg binding located on both the ␤3 MIDAS and ADMIDAS domains, 3,4,36,37 different structural requirements may be required for clot retraction and Fg trafficking.…”
Section: Mutations Affecting Extracellular Domains Of ␤3mentioning
confidence: 99%